Evaluation of the Nijmegen Cochlear Implant Questionnaire in Danish - Neumann, Charlotte Skov; Schmidt, Jesper Hvass (International Archives of Otorhinolaryngology, 2025)
Introduction The Nijmegen cochlear implant questionnaire (NCIQ) is a quantifiable self-assessment health-related quality of life (HRQoL) tool used internationally to determine quality of life (QoL) in cochlear implant (CI) users and to evaluate the implant's subjective benefits.Objective This study aimed to validate the Danish version of the questionnaire (DA-NCIQ) with a test–retest including 60 participants (30 CI users and 30 CI candidates).Methods The intraclass correlation coefficients (ICC) were calculated to evaluate the temporal stability of the participants' answers and the internal consistency of the questionnaire domains was determined using the Cronbach alpha in order to compare these results with the NCIQ's other language versions.Results The DA-NCIQ was found to have Cronbach alpha coefficients between 0.7 and 0.91, as well as test–retest reliability with ICC values between 0.7 and 0.92. These findings were similar to the original and other language versions of this questionnaire. The Cronbach alpha coefficients varied between 0.73 and 0.89, while the ICC test–retest reliability varied between 0.64 and 0.85. Furthermore, the present study found that participants with CIs had an improved HRQoL in all subdomains, except for the advanced sound perception one, when compared to the CI candidates.Conclusion The results supported the DA-NCIQ as a reliable instrument to measure the subjective benefits of CIs in postlingually deafened/hearing-impaired adults.
Keywords: cochlear implant; Nijmegen cochlear implant questionnaire; quality of life; cochlear implant surgery; DA-NCIQ